Crystal structure of nonstructural protein 10 from the severe acute respiratory syndrome coronavirus reveals a novel fold with two zinc-binding motifs - Joseph, Jeremiah S; Saikatendu, Kumar Singh; Subramanian, Vanitha; Neuman, Benjamin W; Brooun, Alexei; Griffith, Mark; Moy, Kin; Yadav, Maneesh K; Velasquez, Jeffrey; Buchmeier, Michael J; Stevens, Raymond C; Kuhn, Peter (Journal of virology, 2006)
The severe acute respiratory syndrome coronavirus (SARS-CoV) possesses a large 29.7-kb positive-stranded RNA genome. The first open reading frame encodes replicase polyproteins 1a and 1ab, which are cleaved to generate 16 "nonstructural" proteins, nsp1 to nsp16, involved in viral replication and/or RNA processing. Among these, nsp10 plays a critical role in minus-strand RNA synthesis in a related coronavirus, murine hepatitis virus. Here, we report the crystal structure of SARS-CoV nsp10 at a resolution of 1.8 A as determined by single-wavelength anomalous dispersion using phases derived from hexatantalum dodecabromide. nsp10 is a single domain protein consisting of a pair of antiparallel N-terminal helices stacked against an irregular beta-sheet, a coil-rich C terminus, and two Zn fingers. nsp10 represents a novel fold and is the first structural representative of this family of Zn finger proteins found so far exclusively in coronaviruses. The first Zn finger coordinates a Zn2+ ion in a unique conformation. The second Zn finger, with four cysteines, is a distant member of the "gag-knuckle fold group" of Zn2+-binding domains and appears to maintain the structural integrity of the C-terminal tail. A distinct clustering of basic residues on the protein surface suggests a nucleic acid-binding function. Gel shift assays indicate that in isolation, nsp10 binds single- and double-stranded RNA and DNA with high-micromolar affinity and without obvious sequence specificity. It is possible that nsp10 functions within a larger RNA-binding protein complex. However, its exact role within the replicase complex is still not clear.